Development and initial validation of the Styles of Emotion Regulation Questionnaire. (October 2021) - Murphy, Samuel T.; Cheavens, Jennifer S.; Strunk, Daniel R.
Abstract: Background: In cognitive behavioral therapies, patients work to develop or strengthen various emotion regulation skills. Understanding the role of such skills in treatment and how focusing on different skills might be used to effectively personalize treatments requires a measure suited to these purposes. With this goal in mind, we developed the Styles of Emotion Regulation Questionnaire (SERQ) to capture individual differences in the broad range of emotion regulation skills taught in these therapies, suited for assessing skills among treatment naïve participants and those participating in treatment. Methods: In this study, 512 participants completed the SERQ. We conducted separate factor analyses of items assessing frequency of skill use and the extent to which skills were impaired when upset. Results: Analyses suggested four skill factors and one emotionally impaired coping factor. In 17 of 20 tests, SERQ scores were related to anxiety, depression, stress, and features of borderline personality disorder. Discussion: Initial results suggest the potential of the SERQ as a measure of emotion regulation strategies taught in cognitive behavioral therapy. We encourage future research using the SERQ in clinical contexts. Highlights: Introduce the Styles of Emotion Regulation Questionnaire (SERQ) The SERQ offers a broad assessment of cognitive behavioral therapy (CBT) skills. Includes four CBT skill factors and one emotionally impaired coping factor SERQ skill scores were negatively related to psychological symptoms in most tests. Emotionally impaired coping was positively related to psychological symptoms.